The Effectiveness of Ivan Pavlov's Counseling Behavior with Modeling Techniques to Improve the Character of Arguing Others Opinions Logically Through Lesson Study - Indah Safitri; I Ketut Gading; I Ketut Dharsana (International Conference on Technology and Educational Science)
This study aims to determine the effectiveness of behavioral counseling modeling techniques to improve the character of Ivan Pavlov others refute logically through the lesson study. The research is a quasi-experimental design with a pretest-posttest control group. This study used a population of 60 students, with a sample of 30 students. Methods of data collection using 30 item questionnaire characters. The results of the data analysis tcount 2.41 > 1.69 ttable so Ho rejected, and Ha accepted. So there is a significant difference. It can be concluded that behavioral counseling Ivan Pavlov with effective modeling techniques to improve the character of others refutes logically